Pertanggungjawaban Pidana Korporasi sebagai Penyelenggara Sistem Elektronik dalam Tindak Pidana Siber di Indonesia - Amanda, Gladys; Usman; Siregar, Elizabeth (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the regulation and construction of corporate criminal liability in its capacity as an Electronic System Provider (ESP) regarding cybercrimes in Indonesia. The rapid development of information technology allows corporate platform providers to become the infrastructure for cybercrimes committed by users. The main issue lies in the legal vacuum regarding the limits of liability for corporations that are passive or engage in omission toward illegal content within the systems they manage. Using a normative legal research method, this study analyzes the synchronization between the ITE Law and the National Criminal Code (Law No. 1 of 2023). The results indicate that current regulations still emphasize active corporate actions; thus, legal reforms are needed to regulate the parameters of liability for negligence or the failure of ESPs to prevent cybercrimes to ensure legal certainty and public protection.